KEEFEKTIFAN PENERAPAN KURIKULUM MERDEKA DI SDN GUGUS I GUNUNGSARI - DEWI, EVA ROSDIANA; ASRIN, ASRIN; AMRULLAH, LALU WIRA ZAIN; HUSNIATI, HUSNIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to find out how effective the implementation of the independent curriculum referring to 3 indicators: Implementation of the project to strengthen the profile of Pancasila students (P5), Implementation of literacy and numeracy programs, and Implementation of differentiated learning and adapting learning to local content. The type of research used in this research is descriptive qualitative. This research was conducted at SDN Gugus I Gunungsari which consists of 9 schools but the researchers only took 3 schools as research subjects: SDN 1 Penimbung, SDN 1 Bukittinggi and SDN 2 Mekarsari. The effectiveness of implementing the independent curriculum was using observation, interviews and documentation instruments. Based on the research results, it was found that the implementation of the project to strengthen the profile of Pancasila students (P5) was carried out starting from the planning, action and reflection stages, guided by the project module prepared by the P5 team formed by the school. The P5 program is carried out in accordance with the 7 themes launched by the Ministry of Education and Culture and each school chooses a theme that suits the surrounding environment and the needs of students. The implementation of the literacy and numeracy program is carried out in accordance with the stages of the School Literacy Movement (GLS) and the phases of the students. There are reflections in the form of tests and non-tests to determine the implementation of the literacy and numeracy program. The application of differentiated learning is carried out using a group learning model and the use of learning media to accommodate students' needs. For differentiated learning has implemented 2 learning content, English and Sasak language content. Based on the research results, it can be concluded that the implementation of the independent curriculum at SDN Gugus I Gunungsari is said to be effective. ABSTRAKPenelitian ini bertujuan untuk mengetahui bagaimana keefektifan penerapan kurikulum merdeka dengan mengacu pada 3 indikator yakni: Penerapan projek penguatan profil pelajar pancasila (P5), Pelaksanaan program literasi dan numerasi, serta Penerapan pembelajaran berdiferensiasi dan penyesuaian pembelajaran muatan lokal. Jenis penelitian yang digunakan dalam penelitian ini ialah kualitatif deskriptif. Penelitian ini dilakukan di SDN Gugus I Gunungsari yang terdiri dari 9 sekolah. Namun peneliti hanya mengambil 3 sekolah sebagai subjek penelitian yakni: SDN 1 Penimbung, SDN 1 Bukittinggi dan SDN 2 Mekarsari. Dalam hal ini keefektifan penerapan kurikulum merdeka diamati secara langsung menggunakan instrumen observasi, wawancara dan dokumentasi. Berdasarkan hasil penelitian didapati bahwa penerapan projek penguatan profil pelajar pancasila (P5) dijalankan mulai dari tahap perencanaan, aksi dan refleksi dengan berpedoman pada modul projek yang disusun oleh tim P5 yang dibentuk oleh sekolah. Pelaksanaan program P5 dijalankan sesuai dengan 7 tema yang diluncurkan oleh kemendikbudristek dan masing-masing sekolah memilih tema yang sesuai dengan keadaan lingkungan sekitar dan kebutuhan peserta didik. Untuk pelaksanaan program literasi dan numerasi dijalankan sesuai dengan tahapan Gerakan Literasi Sekolah (GLS) dan fase-fase peserta didik. Terdapat refleksi berupa tes dan non-tes untuk mengetahui keterlaksanaan program literasi dan numerasi. Untuk penerapan pembelajaran berdiferensiasi dilakukan dengan model pembelajaran berkelompok dan penggunaan media pembelajaran untuk mengakomodir kebutuhan peserta didik. Khusu untuk pembelajaran berdiferensiasi, sekolah telah menerapkan 2 muatan pembelajaran yakni muatan Bahasa Inggris dan Bahasa Sasak. Berdasarkan hasil penelitian, maka dapat disimpulkan bahwa penerapan kurikulum merdeka di SDN Gugus I Gunungsari dikatakan efektif.